BROWN SEAWEED (Sargassum ilicifolium) AS A NUTRITIONAL SUPPLEMENT: EFFECTS ON GROWTH AND HEMATOLOGY IN Labeo rohita - Rafia Zulfiqar; Farkhanda Asad; Basim. S. A. Al Sulivany; Saba Naseer; Irtisha Kanwal; Aiman Nadeem; Muhammad Owais (Science Journal of University of Zakho)
This experimental trial aimed to evaluate the impact of dietary supplementation with Sargassum ilicifolium on the growth performance and hematology of Labeo rohita. Fingerlings weighing an average of 2.36g were allocated into the control and three treatment groups (3%, 5%, and 7% BSW), each with triplicate (25 fingerlings/aquarium) for 90 days after acclimatized for two weeks. The results indicated that the highest growth rate (P<0.05) occurred in the T3 treatment group, with a final weight of 5.31±0.00a, followed by T2 (4.84±0.01b), and T1 (4.63±0.00c), while the lowest growth was observed in the control group (4.20±0.02d).  Maximum weight gain was recorded in T3, which contained the highest level of Sargassum supplementation. Other treatments also showed higher weight gain than the control group. Specific growth rate and protein efficiency were also observed to be higher in treatment groups, particularly in T3, than in the control group. Hematological profiles, i.e., red blood cells (RBCs), white blood cells (WBCs), Hemoglobin (Hb), Hematocrit (HCT), blood indices and leukocytes count also showed better results in T3 and other treatments as compared to the control group.  These findings suggest a high inclusion of sargassum is most effective for promoting the growth and enhancement of the hematology of Labeo rohita, and it is an environmentally sustainable way, as it is economical, environmentally friendly, and readily available alternative for aquaculture.